2001
DOI: 10.1053/joca.2001.0470
|View full text |Cite
|
Sign up to set email alerts
|

Laterally elevated wedged insoles in the treatment of medial knee osteoarthritis: a prospective randomized controlled study

Abstract: This study failed to demonstrate a relevant short-term symptomatic effect of laterally-wedged insoles in medial femoro-tibial OA. However, the decrease in NSAIDs consumption together with better compliance in the treated group are in favor of a beneficial effect of laterally-wedged insoles in medial femoro-tibial OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 9 publications
4
80
0
7
Order By: Relevance
“…This dubiousness is supported by the fact that clinical studies about the effect of wedges come to controversial results. [8][9][10][11] Load reductions within or above 5-10% may also be achieved by other gait modifications such as increased lateral trunk lean, reduced walking speed or by using a contralateral crutch or cane. 33 Greater medial force reductions can also be expected when walking with (more inconvenient) valgus braces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dubiousness is supported by the fact that clinical studies about the effect of wedges come to controversial results. [8][9][10][11] Load reductions within or above 5-10% may also be achieved by other gait modifications such as increased lateral trunk lean, reduced walking speed or by using a contralateral crutch or cane. 33 Greater medial force reductions can also be expected when walking with (more inconvenient) valgus braces.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the use of lateral wedges led to significant pain reduction, [5][6][7] but no pain-relieving effect of lateral wedges was found by other short-and long-term studies. [8][9][10][11] Reductions of the peak EAM when walking with lateral wedges have been shown by several studies.…”
mentioning
confidence: 99%
“…Most new biomechanical evaluations of lateral wedges published since 2011 agree with these findings [41][42][43]. Unfortunately, the assumption that the loadreducing effects of lateral wedges will translate into clinically meaningful reductions in pain in people with knee OA has not been borne out in the clinical trials conducted to date [44][45][46][47]. Of note, the latest RCT, involving 200 people with medial knee OA and published in BMJ in 2011 [48 •• ], demonstrated that lateral wedges worn over 12 months do not significantly reduce pain or slow structural disease progression (as measured via cartilage volume on MRI).…”
Section: Role Of Footwear and Insoles In The Management Of Knee Oamentioning
confidence: 86%
“…The effect on subjective scores showed significant improvements in some, 22 but not all studies. 23,24 Two randomised controlled trials by Maillefert et al 23 and Baker et al 24 did not show statistically significant changes in WOMAC scores with lateral-wedged insoles, although there was a significant reduction in non-steroidal antiinflammatory drug intake in the insole group.…”
mentioning
confidence: 96%